Probiotics Alleviated Nonalcoholic Fatty Liver Disease in High-Fat Diet-Fed Rats via Gut Microbiota/FXR/FGF15 Signaling Pathway. (18th August 2021) - Luo, Minmin; Yan, Junbin; Wu, Liyan; Wu, Jinting; Chen, Zheng; Jiang, Jianping; Chen, Zhiyun; He, Beihui
Abstract : Gut microbiota (GM) dysbiosis and bile acid (BA) metabolism disorder play an important role in the pathogenesis of nonalcoholic fatty liver disease (NAFLD). Probiotics had a beneficial effect on NAFLD, but further study is needed to explore probiotics as a potential therapeutic agent to NAFLD. The aim of this study was to investigate the regulatory effect of probiotics on gut microbiota in NAFLD rats and to explore the possible mechanism of probiotics regulating the bile acid receptor farnesoid X receptor/growth factor 15 (FXR/FGF15) signaling pathway in rats. We established a rat model of NAFLD fed with a high-fat diet (HFD) for 14 weeks, which was given different interventions (312 mg/kg/day probiotics or 10 mg/kg/day atorvastatin) from the 7 th week. Serum lipids and total bile acids (TBA) were biochemically determined; hepatic steatosis and lipid accumulation were evaluated with HE staining. The expression levels of FXR, FGF15 mRNA, and protein in rat liver were detected. 16S rDNA was used to detect the changes of gut microbiota in rats. Compared with the HFD group, probiotics and atorvastatin significantly reduced serum lipids and TBA levels. And probiotics increased dramatically the expression of FXR, FGF15 mRNA, and protein in the liver. But there were no significant changes in the atorvastatin group. Probiotics and atorvastatin can upregulate the diversity of gut microbiota and downregulate the abundance of pathogenic bacteria in NAFLD model rats. In summary, probiotics alleviated NAFLD in HFD rats via the gut microbiota/FXR/FGF15 signaling pathway.